Emigration with a pulled handbrake: Friedrich A. Lutz's internal Methodenstreit - Lachezar Grudev (Duke University, Center for the History of Political Economy (CHOPE), 2021)
My paper reconstructs the path of German economist Friedrich A. Lutz (1901−1975) to American economics. The correspondence with his former teacherWalter Eucken, the founder of the Freiburg School, constitutes a crucial and yet unexplored source for the paper. Through Lutz's case, I demonstrate the growing gulf between German and Anglo-Saxon economics during the late 1930s. In his native Germany, Lutz was trained in methodologically and institutionally focused economics, which differed fundamentally from the mathematical economics dominating Anglo- Saxon academia. He realized that an academic career in the US would be impossible if he did not adapt to the new methods, and if he did not abandon the methods of the German tradition. This gave rise to his internal Methodenstreit. After the emigration in 1938, he constantly experienced doubts and tensions because he was convinced that without considering institutions, mathematical economics was doomed to fail to explain the occurrence and essence of macroeconomic phenomena. Despite his stellar career at Princeton, it was only after 1953 at Zurich, where he taught history and theory of socioeconomics for the rest of his life, that Lutz could reconcile this internal Methodenstreit.
Keywords: A11; B22; B25; B31; B41; E32; 330; Friedrich A. Lutz; Walter Eucken; Friedrich A. Hayek; Emigration; Freiburg School; Ordoliberalism; History of Macroeconomics